Eye Movement Study on Attention Bias to Body Height Stimuli in Height Dissatisfied Males - Chen, Fuguo; Liu, Jie; Chen, Shuanghong; Chen, Hong; Gao, Xiao (Frontiers in Psychology, 2017)
The present study investigated attentional biases in response to height-related words among young men in China. A total of 47 (26 high height dissatisfied (HHD) and 21 low height dissatisfied (LHD)) men performed a dot-probe task. Eye movement (EM) recordings showed that compared to LHD men, HHD men demonstrated an avoidance bias in response to height-related words as revealed by less frequent first fixations on both tall-related and short-related words, and significantly shorter first fixations on short-related words. There were no other significant differences in EM indices (i.e., first fixation latency and gaze duration) between the two groups. In addition, HHD participants were significantly slower than LHD participants in responding to probes that were preceded by short-related words, while there was no difference in response to probes that were preceded by tall-related or neutral words. In sum, the present results indicate that HHD men selectively avoid cues related to shortness in body height.